Population Data of Commercial Ships in Indonesia for Supporting Sea Toll Program and World Maritime Fulcrum - Soetardjo, Meitha; Bisri, A (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
The economic condition of a country is not separated by natural resources as a provider of human needs Indonesia is a maritime country that most of its territory in the form of waters. The shipyard industry is a maritime undertaking whose activities build a new ship, ship maintenance, ship repair etc. The growth of shipbuilding industry in line with the rapid growth of iron and steel mining and advances in machining technology in the late 18th and early 19th centuries. This has made the shipbuilding industry progressing rapidly to date. For preliminary data as a guideline for increasing shipyard capabilities to produce new vessels including docking, it is necessary to inventory the current condition of the shipyard. The shipbuilding industry is one of the maritime industry based on the technology chosen by the government to be developed related to the realization of the maritime shaft program. The technological conditions in the conventional national shipyards that are still not convincingly resized, require the evaluation process to produce a plan and the realization of targeted improvements. The development of the national maritime industry as a solution of the Indonesian government's program to improve the national shipping capability in the transportation of goods and inter-island passengers. The need for vessels in large quantities to exploit existing marine potentials, the need for a fleet of vessels to become goods transport and passengers connecting between islands and between countries, the need for ships for marine and coastal protection, and the need for other special vessels is an urgent matter to be met. Consumers who require shipbuilding services include oil companies, shipping, tourism, transportation, etc. The results of the shipping industry in shipbuilding activities are tankers, ferry boats, fishing boats, yachts, etc.